The effect of inhibin B on ovarian response in subjects with polycystic ovary - Hassan, Affan E.; Sudek, Hanan L.; Abd-alwahab, Taghrid H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Inhibin B hormone is one of the indicative parameters in measuring ovarian reserve ,which is important to be evaluated, since it is one of the markers of the female reproductive potential especially in polycystic ovary patients (PCOS) which is a common cause of anovulatory infertility. Patients and methods: Ninty four infertile polycystic ovaries women, attending the infertility clinic at Baghdad teaching hospital, during the period of October 2005 to December 2006, were compared to 62 control group women who have unexplained infertility. After exact history and examination, inhibin level measurement was done in cycle day 3, the patients are divided according to age into 2 groups (more than 35 years and less than 35 years) .Ovarian stimulation by one of 3 protocols (clomiphene citrate (CC), CC + gonadotropins, goadotropins alone) was applied. Then the ovarian response is measured after that. Results: It was found that inhibin is significantly higher in PCOS patients as compared to control [201.1 ±122.40 vs 71.81 ± 40.63 pg/ml] (P=0.0003).After treatment with ovulation induction drugs, those who are less than 35 years with inhibin level less than 75 pg/ml, have no significant difference in response between the 3 protocols, while in those with inhibin more than 75 pg/ml the response was significantly high to protocol 1(CC only). In more than 35 years patients with inhibin level less than 75 pg/ml ,there was no significant difference in response between protocols while in those with inhibin more than 75 pg/ml the response was significantly higher to protocol 2 (CC+ Gonadotropins). Conclusion: Polycystic ovary patients have significantly higher concentration of inhibin B. Young patients less than 35 years with inhibin level less than 75 pg/ml showed no difference in response between the 3 protocols (CC, CC+ Gonadotropins, and Gonadotropins), while those with higher inhibin level ,the response was significantly higher to protocol 1. In older patients with inhibin more than 75 pg/ml there is no significant difference in response among the 3 protocols.